Closed versus open treatment of mandibular condylar process fractures: A meta-analysis of retrospective and prospective studies. Issue 8 (October 2015) - Berner, Tanja; Essig, Harald; Schumann, Paul; Blumer, Michael; Lanzer, Martin; Rücker, Martin; Gander, Thomas
Abstract: Introduction: The treatment of fractures of the mandibular process remains controversial, although there is a trend towards open reduction and internal fixation. This study compared open and closed treatments and assessed the results with a meta-analysis. Materials and methods: A literature search of PubMed found eight studies that met the search criteria and were included in the meta-analysis. Results: The studies increasingly suggest better results for open treatment, in terms of mouth opening, protrusion, laterotrusion, pain, and malocclusion. In the meta-analysis, the outcome was significantly better for laterotrusion and protrusion in patients treated by open reduction and internal fixation. Conclusion: Due to the different study protocols and lack of information on classification, follow-up time, and inclusion criteria, comparison of the studies remains difficult and further prospective, randomized studies should examine these issues.